Global high-resolution gridded dataset of N2O Emission and mitigation potential from maize and wheat fields - Tesfaye, Kindie; Takele, Robel; Sapkota, Tek Bahadur; Khatri-Chhetri, Arun; Solomon, Dawit; Stirling, Clare; Albanito, Fabrizio (Elsevier, 2021)
This data article provides a high-resolution raw data on Nitrous Oxide (N2O) emission and its mitigation potential from global maize and wheat fields. The analytical results, discussion and conclusion thereof is presented in the related manuscript “Model Comparison and Quantification of Nitrous Oxide Emission and Mitigation Potential from Maize and Wheat Fields at a Global Scale”. This raw dataset has a spatial resolution of 0.0833° × 0.0833°, and comprises pixel level baseline emissions estimated using four empirical N2O emission models (CCAFS-MOT, IPCC Tier-I, IPCC Tier-II and Tropical-N2O) and the model results were validated using experimental data extracted from the literature. Spatially explicit soil, climate and crop management data were obtained from various sources detailed in “Experimental Design, Materials and Methods” section below. N2O mitigation potential were then quantified under four scenarios of excess nitrogen reduction (i.e. 25%, 50%, 75% and 100% reduction of excess nitrogen). We believe that the dataset is a valuable source of information to assess N2O emissions and mitigation measures from maize and wheat fields and to make informed decision. Countries can use this dataset to determine emissions reduction targets in their nationally determined contributions (NDCs) from agricultural sector.